Effect Of Salinity And Seasonality On The Health Status And Mucosal Immunity Performance Of Atlantic Salmon Skin And Its Association With The Caligus Rogercresseyi Infestation In Marine Farms At The Aysén Region (SALTSEA-LICE) - Reyes-Lopez, Felipe Esteban (2025)
Fondecyt Regular Fondecyt Regular 2025 Proyectos de Investigación $ 253621000 IR Aprobado